2007
DOI: 10.4103/0971-6866.34709
|View full text |Cite
|
Sign up to set email alerts
|

Distribution profile of paraoxonase phenotypes among the Gujaratis

Abstract: BACKGROUND:Paraoxonase (PON1) can hydrolyze organophosphate pesticides (OP) and has a key role in the susceptibility of human in OP toxicity. The human-enzyme shows polymorphism and variations in the distribution profile of its phenotypes among different ethnic groups have been observed.AIMS:To see the distribution pattern of total PON1 activity in 45 healthy attendants of poisoning cases; 121 healthy unrelated farm-labours and 59 normal subjects of trauma.MATERIALS AND METHODS:The PON1 activities from serum/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…The capacity of paraoxonase to hydrolyze lipid peroxides was found to be the reverse of paraoxon hydrolytic activity, showing that phenotype A with low paraoxonase activity is more protective against lipid modification than phenotype B. The distribution of paraoxonase activity in the studied population was trimodal and presented low (type A), high (type B) and intermediate (type AB) activity, which is in accordance with other studies [ 14 , 38 , 39 ]. The odds ratio and the relative risk analysis showed that the patients with moderate ischemia are much more often characterized by phenotype A than phenotype B and the control group.…”
Section: Discussionsupporting
confidence: 90%
“…The capacity of paraoxonase to hydrolyze lipid peroxides was found to be the reverse of paraoxon hydrolytic activity, showing that phenotype A with low paraoxonase activity is more protective against lipid modification than phenotype B. The distribution of paraoxonase activity in the studied population was trimodal and presented low (type A), high (type B) and intermediate (type AB) activity, which is in accordance with other studies [ 14 , 38 , 39 ]. The odds ratio and the relative risk analysis showed that the patients with moderate ischemia are much more often characterized by phenotype A than phenotype B and the control group.…”
Section: Discussionsupporting
confidence: 90%
“…La paraoxonasa es una enzima polimórfica que protege contra la exposición a POFs, ya que cataliza la hidrólisis de los ésteres de los POFs a compuestos excretables menos dañinos, tal como el paraoxón, (un metabolito de degradación del paratión) y del cual se deriva su nombre. La PON1 juega un rol principal en la susceptibilidad a la toxicidad a POFs y los individuos con actividad baja de paraoxonasa están más predispuestos a desarrollar los síntomas de la intoxicación (Patel et al, 2007).…”
Section: Introductionunclassified